Commentary: Systems biology approach to model the life cycle of Trypanosoma cruzi - Carrea, Alejandra (2017)
In a recent work we have identified, from a bigger gene regulatory network, a seven-node moduleinvolved in the control of the life cycle of Trypanosoma cruzi (T. cruzi) (Carrea and Diambra,2016). To that end, we have analyzed microarray gene-expression data of the four differentT. cruzi?s life cycle stages, by means of a systems biology approach. The found module is thesmallest gene regulatory subnetwork able to emulate the dynamical properties of the parasite.This module is composed of nine genes: three of them coding for uncharacterized proteins, andthe other six genes coding for characterized proteins. The latter code for: a hexokinase, a δ-1-pyrroline-5-carboxylate dehydrogenase, a quinone oxidoreductase, a glutamate dehydrogenase, apeptidyl-prolyl cis-trans isomerase, and a metaciclina II. Except for metaciclina II, these genes codefor proteins involved in metabolic pathways. Thus, we were expecting gene-expression regulatoryproteins instead of the striking information we obtained. Yet, it eventually became clear that thesemetabolic enzymes could have other regulatory functions beyond their known metabolic one. Thistype of multifunctional proteins are known as moonlighting proteins (Jeffery, 1999). They were firstdiscovered in the late 1980s by Piatigorsky et al. (1988). They found that the lens structural proteinδ-crystallin and the metabolic enzyme argininosuccinate lyase are both encoded by the same gene inducks. Today, it is well-known that moonlighting proteins comprise diverse kinds of proteins, andthat they are present in many different organisms including animals, plants, yeasts, prokaryotes,and protists (for reviews see Jeffery, 2009; Huberts and van der Klei, 2010; Jeffery, 2014).